Belief systems, religion, and behavioral economics : marketing in multicultural environments - Minton, Elizabeth A., (2014 digital library., 2014)
Religion is a topic that businesses often ignore, in spite of 70% of the world being religious. Whether the silence results from the taboo nature of the topic or the thought that religion is a separate domain from consumption and business, it cannot be denied that it has received scant attention. Many do not realize (or resist) the idea that religion is a key contributor to a consumer's core values, which then contribute to consumption decisions, voting practices, reaction to pro-social messages and public policy, as well as donating behavior.